The effects of walking and cycling computer workstations on keyboard and mouse performance. - Straker L; Levine J; Campbell A; Straker, Leon; Levine, James; Campbell, Amity (Human Factors, 2009)
Objective: This study aimed to determine the effects of active workstation designs on speed and error during typing, mouse pointing, and combined type and mouse-use tasks.Background: Office ergonomics has focused on musculoskeletal disorder prevention; however, increasing computer-based work also increases health risks associated with inactivity. Workstations allowing computer users to walk or cycle while performing computer tasks have been shown to demand sufficient energy expenditure to result in significant health benefits. However the performance effects of being active while using a computer have not been documented.Method: Thirty office workers (16 female, 15 touch typists) performed standardized computer tasks in six workstation conditions: sitting, standing, walking at 1.6 km/h and 3.2 km/h, and cycling at 5 and 30 watts. Performance, perceived performance, and heart rate were measured.Results: Computer task performance was lower when walking and slightly lower when cycling, compared with chair sitting. Standing performance was not different from sitting performance. Mouse performance was more affected than typing performance. Performance decrements were equal for females and males and for touch typists and nontouch typists.Conclusion: Performance decrements maybe related to both biomechanical and cognitive processes. Active workstations may be less suitable for mouse-intensive work and susceptible users.Application: Although active workstations may result in some decrement in performance, their ability to increase daily energy expenditure may make them a feasible solution for workplace inactivity.